Sarah Sze - Enwezor, Okwui; Buchloh, B. H. D.; Hoptman, Laura J., 1962-; Sze, Sarah, 1969- (London ; New York, NY : Phaidon Press Ltd., 2016)
The first substantial monograph on an artist whose sculptures captur e the proliferation of information and objects in contemporary life. Sa rah Sze (b. Boston, 1969, lives and works in New York) has developed a sculptural aesthetic that transforms space through radical shifts in sc ale, colonizing peripheral spaces, engaging with the history of a build ing, and altering the viewer's perception and experience of architectur e through large, site-specific interventions. Known for her unexpected and carefully arranged combinations of materials, from cotton buds and tea bags to water bottles and ladders, light bulbs and electric fans, S ze has presented ephemeral installations that penetrate walls, suspend from ceilings and burrow into the ground. Her work exists at the inters ection of sculpture, drawing and architecture where her formal interest in light, air and movement is coupled with an intuitive understanding of colour and texture. Like the scientific instruments of measurement t hey often reference, Sze's sculptures attempt to quantify and organize the universe, ascribing a fragile, personal system of order. Within her practice, sculpture becomes both a device for organizing and dismantli ng information and a mechanism to locate and dislocate oneself in time and space. Sze received a BA from Yale University in Connecticut in 199 1 and an MFA from New York's School of Visual Arts in 1997. She is repr esented by Tanya Bonakdar in New York and Victoria Miro in London. In 2 013 she represented the United States at the 55th Venice Biennale. She was the recipient of a MacArthur Fellows Program Genius Grant in 2003 a nd of the AICA Award for Best Project in a Public Space in 2012.
Includes bibliographical references.
Keywords: Sze, Sarah, -- 1969- -- Themes, motives; Sze, Sarah, -- 1969- -- Interviews; Sze, Sarah, -- 1969-; Sculpture -- 21st century -- Pictorial works; Installations (Art) -- 21st century -- Pictorial works; Arts, Modern -- 20th century -- Pictorial works; Artists -- United States -- 21st century; Installation; Interviews; Pictorial works